Kebijakan Kriminal Dalam Menanggulangi Kejahatan Delik Agama - Endri ' (Jurnal Ilmu Hukum, 2013)
Pancasila, especially the first principle of the "Belief in God Almighty" respect and collaboration among religious followers and the adherents of different beliefs. In everyday practice, the cases relating to religious offenses, such as humiliation, degrading, incitement and defamation against certain religions and the destruction of places of worship performed by an individual or group of people or organizations are still happening amongst the people. Criminal policy in tackling crime offense religion in Indonesian positive law contained in the Criminal Code and Law No. 1 of 1965 on Pnps, there are still weaknesses.